1443A causal mediation analysis of the effect of disability on mental health mediated by employment. (2nd September 2021) - Aitken, Zoe; Simpson, Julie; Bentley, Rebecca; Kavanagh, Anne
Abstract: Background: There is evidence that disability acquisition causes a decline in mental health, but few studies have examined the causal mechanisms through which the effect operates. This study used a novel approach to mediation analysis to quantify interventional indirect effects through employment and income. Methods: We used four waves of longitudinal data to compare self-reported mental health between working aged individuals who acquired a disability (n = 233) and those who remained disability-free (n = 5419). We conducted a causal mediation analysis quantifying interventional indirect effects of disability acquisition on mental health operating through two distinct mediators: employment status and income. We used multiple imputation with 50 imputed datasets to account for missing data. Results: The total causal effect of disability acquisition on mental health was estimated to be a 4.8-point decline in mental health score (estimated mean difference: -4.8, 95% CI -7.0, -2.7). The interventional indirect effect through employment was estimated to be a 0.5-point difference (-0.5, 95% CI -1.0, 0.0), accounting for 10.6% of the total effect, whereas there was no evidence that income explained any of the effect. Conclusion: This study estimated that disability-related mental health inequalities could be reduced by 10.6% if employment rates were the same for people with disabilities as those without. The results highlight the need to implement measures to enable people with disabilities to remain in employment and improve employment and vocational training opportunities for people who acquire a disability.